Keterkaitan Antara Bidang Orthodonti dan Periodonti dalam Perawatan Estetika Rongga Mulut - Trijani Suwandi (Jurnal Kedokteran Gigi Terpadu, 2020)
Background: Orthodontic Treatment aims to correct occlusion functional and  aesthetics as well as achieving  the health of supporting structure. Orthodontists frequently treat patients with periodontal problems both from aesthetic considerations as discrepancy gingival margin and functional considerations due to periodontal disease.  Review: The relationship between orthodontics and periodontics is very important in establishing the diagnosis and treatment plan, and this relationship often resembles   symbiosis. In many cases periodontal health can be improved with orthodontic movements, and orthodontic tooth movement is often facilitated by periodontal therapy.  But on the other hand orthodontic treatment can also cause periodontal problems such as gingival inflammation, recession, bone dehiscence.  Conclusion: This paper summarizes the literature to provide a basic understanding of interrelationship between periodontics and orthodontics for optimized treatment outcomes.